Pelargonium sidoides extract EPs 7630: a review of its clinical efficacy and safety for treating acute respiratory tract infections in children - Careddu D; Pettenazzo A (International Journal of General Medicine, 2018)
Domenico Careddu,1 Andrea Pettenazzo2 1Pediatrics, Italian Health Service, Cameri, Italy; 2Department of Women’s and Children’s Health, University Hospital of Padua, Padova, Italy Background: In numerous randomized controlled trials (RCTs) and systematic reviews such as those published by the Cochrane Collaboration, Pelargonium sidoides extract EPs® 7630 was shown to be effective in acute respiratory tract infections (aRTI) in all investigated age-groups. This narrative review focuses on recently published results from RCTs investigating the clinical efficacy and safety of EPs 7630 in children and adolescents with different manifestations of aRTI, in order to present a broader overview and to provide an update on the state of knowledge regarding the use of EPs 7630 in this age-group.Methods: The Cochrane review on P. sidoides extract for aRTI published by the Cochrane Collaboration was searched for cited RCTs with EPs 7630 in children and adolescents suffering from aRTI. A PubMed and SCOPUS literature search was performed for publications issued before June 13, 2017 (search terms: children, Pelargonium sidoides, EPs 7630, respiratory). Reference lists of publications found were searched for relevant citations. Results: Eight RCTs investigating the application of EPs 7630 in acute bronchitis, acute tonsillopharyngitis, and aRTI in the context of chronic preconditions were identified. Results showed a statistically significant improvement of aRTI symptom severity for EPs 7630 as compared to controls. The investigation of EPs 7630 in asthmatic children and adolescents with aRTI demonstrated a significant symptom-alleviating effect and a possibly associated reduction of asthma attacks. In immunocompromised children with acute upper RTI, an alleviating effect of EPs 7630 was shown. All RCTs reviewed reported good safety and tolerability of EPs 7630.Conclusion: The P. sidoides extract EPs 7630 is effective and safe for those of pediatric age and may be regarded as an alternative option for the management of aRTI. Keywords: Pelargonium sidoides, EPs 7630, children, acute respiratory tract infections, acute bronchitis, asthma